Socialist Song Book [Bladmuziek]. - Bristol Militant Supporters (Bristol : Bristol Militant Supporters.)
Deze brochure bevat volgende liederen
The International
The Red Flag
Bandiera Rossa
The Marseillaise
The 15th Brigade
The Coal-owner And The Pitman' Wife
The Gresford Disaster
Oh dear me
Four-Pence A Day
The Blackleg Miners
The Four Loom Weaver
Way Down In The Mine
The Man That Waters The Workers' Beer
Kevin Barry
I Am A Merry Ploughboy
Hallelujah I'm A Bum
Dump The Bosses Off Your Back
Joe Hill
Scabs In The FActory
The Union Maid
Union Buttons
The Boss Is Having A Terrible Time Parlez-Vous
Detroitium
Pie In The Sky
We Want Nationalisation
The Capitalist Game
Aye Lads
Sing A Song of Sixpence
Leon Trotsky Is A Nazi
Red Flies The Banner Oh!
Deportees
The Leaving Of Liverpool
Over There
The People's Commisars
The H-Bomb's Thunder
One Man Hands
Tilers Of The Nation
Lift Up The People's Banner
Oh Maggie, Maggie Thatcher
Ding Dong Dollar
Harry (Pollità Was A Bolshie?
The March Of The Workers
Eight Hours For Every Worker
Two Songs From World War I
Did You Understand
Engels
Bladmuziek
Keywords: liederen